Penggunaan Model Pembelajaran Snowball Throwing untuk Meningkatkan Hasil Belajar Peserta Didik pada Pembelajaran Matematika Kelas VI SDN 99/X Sidomukti Semester Ganjil Tahun Ajaran 2021/2022 - Anik Martiah (Departement of Mathematics Education, 2022)
The purpose of this study was to obtain information and discuss the use of the Snowball Throwing learning model to improve student learning outcomes in class VI mathematics learning at SDN 99/X Sidomukti in the odd semester of the 2021/2022 academic year. This type of research is classroom action research which consists of two cycles with each cycle consisting of four stages, namely planning, implementation, observation and reflection. This research was conducted at VI SDN 99/X Sidomukti in the odd semester of the 2021/2022 academic year with the research subjects being students of class VI SDN 99/X Sidomukti, totaling 20 students. Data collection techniques using tests, field notes, interviews, and documentation. Data were analyzed using percentages and data reduction. The results showed that the Snowball Throwing learning model could improve the mathematics learning outcomes of the sixth’s grade students of SDN 99/X Sidomukti, marked by the improvement obtained from cycle I to cycle II.